Two-dimensional-Ti3C2 magnetic nanocomposite for targeted cancer chemotherapy - Darroudi, Mahdieh; Elnaz Nazari, Seyedeh; Karimzadeh, Maryam; Asgharzadeh, Fereshteh; Khalili-Tanha, Nima; Asghari, Seyyedeh Zahra; Ranjbari, Sara; Babaei, Fatemeh; Rezayi, Majid; Khazaei, Majid (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Cervical cancer is the leading cause of cancer-related death in women, so novel therapeutic approaches are needed to improve the effectiveness of current therapies or extend their activity. In recent decades, graphene analogs, such as Mxene, an emerging class of two-dimensional (2D) graphene analogs, have been drawing considerable attention based on their intrinsic physicochemical properties and performance as potential candidates for tumor therapy, particularly for therapeutic purposes. Here we explored the targeted drug delivery in cervical cancer in in vivo model. Mxene-based nanocarriers are not able to be precisely controlled in cancer treatment. Method: To solve this problem, the titanium carbide-magnetic core-shell nanocarrier (Ti3C2-Fe3O4@SiO2-FA) is also developed to provide synergetic anticancer with magnetic controlling ability along with pH-responsive drug release. A xenograft model of the cervix was used to investigate the effects of Cisplatin alone, or in combination with Ti3C2@FA and Ti3C2@ Fe3O4@SiO2-FA, on tumor growth following histological staining for evaluation of necrosis. Result and Discussion: A significant tumor-growth suppression effect is shown when the Ti3C2-Fe3O4@SiO2-FA nanocarrier is magnetically controlled Cisplatin drug release. It reveals a synergistic therapeutic efficacy used in conjunction with pharmaceuticals (p < .001). According to the in vivo study, the Ti3C2@FA@Cisplatin nanocomposite exhibits less tumor growth than the drug alone or Ti3C2@FA@Cisplatin via increasing necrosis effect (p < .001). Through this study, Mxene nanosheets are expanded for biomedical applications, not only through the fabrication of biocompatible magnetic Mxene nanocomposite but also through the development of functionalization strategies that enable the magnetic Ti3C2 nanocomposite to load high levels of Cisplatin for cervical cancer treatment (242.5%). Hence, Ti3C2-Fe3O4@SiO2-FA nanocarriers would be promising candidates to improve cancer treatment efficiency.